Celebrations of 50 years of the Acoustic Centre at the Adam Mickiewicz University in Poznań - JORASZ, Urszula (Archives of Acoustics, 2007)
The year 2006 witnessed the 50 anniversary of establishing the Chair of Acoustics and Theory of Vibrations at the Adam Mickiewicz University in Poznań, which was the first and only in the country academic centre of acoustics. In 1985 the Chair was transformed into the Institute of Acoustics being till today a part of the Faculty of Physics at the same university. The main celebrations of the anniversary were held on December 12, 2006 in the vestibule of the Institute of Acoustics. Among the guests taking part in the special meeting organised on this day were: Professor Stefan Jurga - Deputy State Secretary at the Ministry of Science and Higher Education, His Magnificence Professor Stanisław Lorenc - rector of AMU, family members of Professor Marek Kwiek who had created and was the first head of the Chair of Acoustics and Theory of Vibrations, representatives of the Committee on Acoustics at the Polish Academy of Sciences headed by the chairman Professor Andrzej Rakowski, Deans of the Faculty of Physics, the Institute of Acoustics workers and students. There was also a large group of retired professors who remembered Professor Kwiek and worked with Him.